TINDAK TUTUR PERMINTAAN DALAM BAHASA INDONESIA DI KALANGAN MAHASISWA - Listiyorini, Ari (Diksi, 2009)
This study aims to describe the speech act of requests in Indonesian, theirdeterminant factors, and their special functions. The data sources were spoken requests bystudents. The data were collected by taping them and were analyzed by grouping them andinterpreting them contextually. The results show that there are direct and indirect requests.Direct requests are made in imperatives, and indirect requests are made in statements orquestions. Sometimes a combination of an imperative and a question and that of a questionand a question are employed in requests. Politeness in requests is marked by certainexpressions, such as tolong, ayo/yo/yok/yuk, mari, coba, maaf and mohon. The socialcontext influencing the choice of requests includes the intimacy of the speaker andinterlocutor, the speech situation, the age difference between the speaker and interlocutor,and the speaker's cultural background. The special functions of requests include that ofasking for or borrowing an object, of asking the interlocutor to do something, ofwelcoming, of inviting, and of prohibiting.Keywords: speech act, form, function, politeness